1998
DOI: 10.1007/bf03165416
|View full text |Cite
|
Sign up to set email alerts
|

Four cases of Warthin’s tumor of the parotid gland detected with FDG PET

Abstract: In the cancer screening with FDG PET for 1,872 medical health club members, high FDG accumulation in the parotid gland was found in four males (age, 57-70 years). Warthin's tumor was confirmed by surgical pathology. The exact mechanism of high FDG accumulation in Warthin's tumor is not yet known. This tumor may be found incidentally during FDG PET studies. When high FDG accumulation is found in the parotid gland, integrated consideration of the results of the physical examination, medical history and 99mTc-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…c Longitudinal power Doppler sonographic image reveals mild hypervascularity of the mass mas identified by 18 F-FDG PET or PET/CT ranging from 14% to 63% [12,13]. PET also has limited utility for differentiating benign from malignant salivary gland tumors, primarily because of high FDG uptake by some benign salivary gland tumors, especially Warthin tumor [5,6,14,15]. Basu et al [16] reported 25 patients with incidental FDG uptake in the parotid glands: diffuse symmetric in six; diffuse asymmetric in 12; and focal in seven patients.…”
Section: Discussionmentioning
confidence: 97%
“…c Longitudinal power Doppler sonographic image reveals mild hypervascularity of the mass mas identified by 18 F-FDG PET or PET/CT ranging from 14% to 63% [12,13]. PET also has limited utility for differentiating benign from malignant salivary gland tumors, primarily because of high FDG uptake by some benign salivary gland tumors, especially Warthin tumor [5,6,14,15]. Basu et al [16] reported 25 patients with incidental FDG uptake in the parotid glands: diffuse symmetric in six; diffuse asymmetric in 12; and focal in seven patients.…”
Section: Discussionmentioning
confidence: 97%
“…Except the physiological concentration of 18F-FDG, benign lesions with increased FDG uptake are found in more than 25% of the PET/CT studies performed in patients with proven or suspected malignancy, with inflammation being the most common cause [11] . The high FDG uptake in some benign parotid gland tumors, particularly Warthin's tumor, was extensively observed and reported [9,[11][12][13][14] . This tumor may be found incidentally during FDG PET studies.…”
Section: Discussionmentioning
confidence: 95%
“…This tumor may be found incidentally during FDG PET studies. Horiuchi M et al reported in the cancer screening with FDG PET for 1,872 medical health club members, high FDG accumulation in the parotid gland was found in four males (age, 57-70 years), who were finally diagnosed as Warthin's tumor by surgical pathology [14] . In a retrospective study of seventy-two patients with benign parotid gland tumors (n=52), malignant parotid tumors (n=12), and inflammation (n=8), Malignant parotid tumors showed significantly higher FDG uptake (standard uptake values [SUVs]) than both benign tumors and inflammation, except in Warthin's tumor [9] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations